Primary study on the expression pattern and function of zinc metalloproteinase NAS-31 in Haemonchus contortus - HUANG Yan; ZHANG Hui; TONG Danni; ZHOU Jingru; WU Fei; CHEN Xueqiu; YANG Yi; MA Guangxu; DU Aifang (浙江大学学报. 农业与生命科学版)
Haemonchosis is caused by Haemonchus contortus parasitic in the ruminant abomasum. In order to study the function of zinc metalloproteinase NAS-31 gene (Hc-nas-31) in the free-living period (especially L3) of this kind of worm, real-time quantitative polymerase chain reaction (qRT-PCR) was conducted to detect the transcription level of the target gene in different developmental stages of H. contortus. Rapid amplification of cDNA ends (RACE), genome walking and fusion PCR methods were used to amplify Hc-nas-31 gene and the gene structure was analyzed after that. Then, prokaryotic expression plasmid was constructed and transformed into BL21 to express the recombinant protein. A New Zealand white rabbit was immunized with the purified recombinant Hc-NAS-31 (rHc-NAS-31) to prepare polyclonal antibodies, which were used to analyze the expression pattern of Hc-NAS-31 in H. contortus by indirect immunofluorescence assay. The results showed that Hc-nas-31 was transcribed in all stages of the worms, while the transcription level of L3 was the highest. Polyclonal antibody was made successfully and its specific binding with Hc-NAS-31 natural protein was confirmed by Western blotting. Indirect immunofluorescence analysis showed that Hc-NAS-31 protein was mainly expressed in the epithelial syncytia of L3, while in adults, it was distributed in the intestines, gonads, muscle tissues and early eggs. In summary, we confirmed the expression pattern of NAS-31 in H. contortus. This experiment lays the foundation for further research on the biological functions of Hc-nas-31.